Low-complexity algorithm using DCT approximation for POST-HEVC standard - Ben Jdidia, Sonda; Jridi, Maher; Belghith, Fatma; Masmoudi, Nouri (SPIE, 2018)
Under development by the Joint Collaborative Team on Video Coding (JCT-VC), the recent standardization proposal beyond HEVC known as POST-HEVC (or Future Video Coding FVC) proposition was designated to improve the coding efficiency compared to the HEVC. In order to respond to users’ requests for high quality videos in 4k and 8k, this standard is planned to cover a wide range of multimedia applications. When compared with its predecessor, the postHEVC standard should be capable of providing a bit rate reduction of approximately 30% at the same subjective quality given by HEVC. However, this efficiency comes with additional complexity which shall be taken into consideration. In fact, FVC encoders should be capable of trading off complexity and coding efficiency in order to meet real-time requirements or non-real-time requirements when an important coding efficiency is achieved. More specifically, the increased complexity cognized per the transform module should be reconsidered. This complexity can be seen on the introduction of a new approach called Adaptive Multiple Transform (AMT) involving five different transformation types from DCT/DST family for sizes ranging from 4x4 to 128x128. This can be a real issue since the majority of image and video transmission and processing applications are subject to real-time constraints. Hence, to meet these requirements, a large amount of effort has been devoted to eliminate multiplication operations in order to insure low-complexity transform. In this context, the approximation technique can provide eloquent estimations at low-complexity requirements. The contributions of this method can be mainly seen on the reduction of the device utilization and power consumption in addition to lower computational complexity. This gain comes from the elimination of multiplications which require a great number of logical resources. Furthermore, it has been demonstrated in the literature that some approximation transforms can decrease dramatically the hardware resources with slight degradation of the video quality. Accordingly, the approximation technique seems to be an efficient solution offering an adequate compromise between precision and complexity. This work benefits from the DCT-II approximations evoked in previous works in order to minimize the computation time of the transform module as well as its complexity. This idea comes after a statistical analysis done on 4k videos for different quantization parameters which shows that the DCT-II utilization can reach 60% of the total of possible transformation types. In the last version of the paper, we will provide extensive statistical studies on the compressed bitstream. Then, we will use that to detect bottlenecks of the transformations in order to specify the computation elements that should be optimized and approximate.